2010
DOI: 10.1016/j.bbamcr.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Formins in development: Orchestrating body plan origami

Abstract: Formins, proteins defined by the presence of an FH2 domain and their ability to nucleate linear F-actin de novo, play a key role in the regulation of the cytoskeleton. Initially thought to primarily regulate actin, recent studies have highlighted a role for formins in the regulation of microtubule dynamics, and most recently have uncovered the ability of some formins to coordinate the organization of both the microtubule and actin cytoskeletons. While biochemical analyses of this family of proteins have yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 198 publications
(297 reference statements)
2
30
0
Order By: Relevance
“…1B). A role for diaphanous-like formins in cancer progression is supported by previous studies in mammalian models (Nürnberg et al, 2011), and effects of Drosophila Dia on cell motility (Liu et al, 2010), and regulation of imaginal disc growth (Sansores-Garcia et al, 2011) (Fig. 1C).…”
Section: Cher Accumulates In Invasive Clonal Tumorssupporting
confidence: 63%
“…1B). A role for diaphanous-like formins in cancer progression is supported by previous studies in mammalian models (Nürnberg et al, 2011), and effects of Drosophila Dia on cell motility (Liu et al, 2010), and regulation of imaginal disc growth (Sansores-Garcia et al, 2011) (Fig. 1C).…”
Section: Cher Accumulates In Invasive Clonal Tumorssupporting
confidence: 63%
“…This is consistent with a role for FMNL3 in EC elongation, as the processes of vasculogenesis are morphologically distinct to those of angiogenesis and do not require the same polarised elongations (Carmeliet, 2000). Interestingly, although FMNL3 is highly conserved between humans and fish (72% identity), it is absent from Drosophila, which do not carry out angiogenesis and have a single, distantly related FMNL-like protein (Liu et al, 2010). Ciona, which sit at the bottom of the chordate clade, also lack the gene encoding FMNL3 (data not shown).…”
Section: Fmnl3 Is a Cytoskeletal Regulator Of Angiogenesis 1425supporting
confidence: 52%
“…5 Cooperation between the FH1 and FH2 domains regulates the formation of straight actin filaments, 6,7 thereby modulating diverse cytoskeletal reorganization during development of the heart. 8, 9 We have demonstrated that Fhod3 knockout mice display abnormal maturation of muscle fibers in the heart, resulting in embryonic lethality with ventricular hypokinesia. 10 In addition, transgenic mice expressing a mutant FHOD3 protein with Ile1127Ala (I1127A) substitution in the FH2 domain, which is defective in actin-assembling activity, exhibits phenotypic changes similar to DCM.…”
Section: Srf Reporter Gene Activitymentioning
confidence: 99%